Analisis Hukum Ekonomi Syari’ah Tentang Jual Beli Makanan Tanpa Harga - Abdillah, Syaik; Syifaulhuda, Annisa (STAI Al Musaddadiyah Garut, 2023)
Buying and selling food today has a wide range of diversity in its mechanisms. One of them is the mechanism of buying and selling food without price inclusion which is currently popular in several restaurants that apply the concept of buffets. Because there is no price transparency at the beginning, this makes some polemics among consumers. The formulation of the problem in this study is how the mechanism of buying and selling food without prices. As well as how to analyze the economic law of shari'ah about buying and selling food without prices. From several formulations of these problems, the purpose of this study is to determine the mechanism of pricing and analysis of shari'ah economic law regarding buying and selling food without prices. This research is a type of qualitative research using the literature study method which is carried out by presenting data using data alasisance techniques. Based on the results of the research, the sale and purchase is included in the ba'i al-muathah it may be done if both parties agree in the contract process. Regarding the indication of uncertainty (gharar) in the mechanism, it can be avoided by asking for information in advance about the provisions and price information at the restaurant. This is especially true for first-time shoppers. Keywords: shari'ah economic law, buying and selling, food, price;